(untitled) (Journal of Forensic Medicine & Toxicology, 2016)
Homicide refers to the killing of one human being by another human being with or without any intention. A Prospective study of total of 159 homicide cases was done which were brought for autopsy at Sanjay Gandhi Memorial Hospital, Delhi, during the three year period (2011-2014) and analyzed for the various socio demographic factors involved in the homicidal acts. Results showed that the males were commonly victimized in the homicidal acts compared to females. Majority of the victims were in the age group of 21 to 30 years, married, belonged to lower socio-economic status, and hailed from rural areas. Most of the attacks on males occurred at outdoor by the acquaintance and those on females at their house by the spouse. The offenders involved were multiple in 54.71% and single in 32.7% of cases. Majority of the deaths were caused by infliction of mechanical injuries on the body with blunt force trauma accounting for 47.16% of cases.